2017
DOI: 10.1097/sle.0000000000000440
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Weight Loss With the Intragastric Balloon in Patients With Different Degrees of Obesity

Abstract: IGB provided sustained weight loss in patients who remained in dietary follow-up for 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…Considering the total group of patients, the mean weight loss was 19.13 kg, %TWL was 18.42, % EWL was 65.66 and BMI decreased 6.85 kg/m 2 . These results are similar to those observed by Nunes et al (2017) [12] (%TWL of 18.9 and decrease in BMI of 6.76 kg/m 2 ) and are slightly superior to those observed in several other studies [13][14][15][16][17][18][19][20] and in two meta-analyses [21,22]. This greater decrease in body weight could be partly attributed to the balloon volume.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Considering the total group of patients, the mean weight loss was 19.13 kg, %TWL was 18.42, % EWL was 65.66 and BMI decreased 6.85 kg/m 2 . These results are similar to those observed by Nunes et al (2017) [12] (%TWL of 18.9 and decrease in BMI of 6.76 kg/m 2 ) and are slightly superior to those observed in several other studies [13][14][15][16][17][18][19][20] and in two meta-analyses [21,22]. This greater decrease in body weight could be partly attributed to the balloon volume.…”
Section: Discussionsupporting
confidence: 91%
“…Fernandes et al (2016) [26] also observed a significantly higher %EWL in the group with lower baseline BMI (26 -30 kg/m 2 ) compared to the group with higher BMI (> 30 kg/m 2 ) (96% vs. 41%, respectively). Similarly, Nunes et al (2017) [12] and Al-Sabah et al (2016) [18] observed higher %EWL in the group of individuals with lower BMI at baseline. Although %EWL was greater in the subjects presenting pre-obesity, the %TWL was similar across the different degrees of overweight in our participants.…”
Section: Discussionmentioning
confidence: 74%
“…The efficacy of IGB therapy in subjects with a BMI >27–35 kg/m 2 , who may not qualify for formal bariatric surgery, has been demonstrated [ 24 ]. A BMI cut-off of >27 kg/m 2 was therefore chosen for patient selection in this unit.…”
Section: Methodsmentioning
confidence: 99%
“…Given the high cost, complication risk and invasiveness of bariatric surgery, endoscopic treatment such as intragastric balloon (IB) is sometimes presented as a safer and lower-cost option for weight reduction (Hurt et al 2017). IBs are generally placed in the stomach endoscopically to reduce gastric capacity, enhance feelings of fullness and induce weight loss (Hurt et al 2017, Nunes et al 2017, Tate & Geliebter 2017. The IBs are removed after 6 months, as the risk of balloon deflation and possible migration increases substantially after this period (Hurt et al 2017, Nunes et al 2017, Tate & Geliebter 2017).…”
Section: Introductionmentioning
confidence: 99%